The role of the school principal as educational supervisor resident in the professional development of new teachers in the secondary schools of the Directorate of Education Kasbah Irbid - Al Khasawneh, Thabet Mohammed Ali (Journal of Educational and Psychological Sciences, 2018)
The aim of the study was to identify the role of the school principal as educational supervisor in the professional development of new teachers in secondary schools in the Directorate of Education of Irbid, in the fields of (planning for teaching, classroom assessment, classroom management and human relations). The study was based on the descriptive method. The sample of the study consisted of (170) teachers for the academic year (2018/2019), and after excluding the survey sample of (20) teachers, (150) teachers of the new teachers who were appointed at the beginning of the academic year (2018/2019) of different disciplines and educational qualifications. To achieve the objectives of the study, the researcher prepared the questionnaire tool, consisting of (32) paragraphs distributed evenly on the four areas of the questionnaire. The results showed that the role of the school principal as an educational supervisor in the professional development of the new teachers in the fields of professional development as a whole obtained an average of (3.59) and (moderately). On the field level, (3.72), both with a "significant" grade. The field of teaching planning has a mean (3.47) and a grade grade average (3.45), both of which are "intermediate". The results also showed that there were no statistically significant differences between the estimates of the role of the school principal as educational supervisor in the professional development of the new teachers due to the variables of qualification and specialization.